How can nanotechnology help membrane vesicle-based cancer immunotherapy development? - Tian, Xin (Landes Bioscience, 2013)
Exosomes are nanosized vesicles originating from endosomal compartments and secreted by most living cells. In the past decade, exosomes have emerged as potent tools for cancer immunotherapy due to their important roles in modulation of immune responses, and promising results have been achieved in exosome-based immunotherapy. The recent rapid progress of nanotechnology, especially on tailored design of nanocarriers for drug delivery based on both passive and active targeting strategies, sheds light on re-engineering native membrane vesicles for enhanced immune regulation and therapy. Applications of nanotechnology toolkits might provide new opportunity not only for value-added therapeutic or diagnostic strategies based on exosomes in cancer immunotherapy, but also new insights for biogenesis and biological relevance of membrane vesicles. This commentary focuses on the recent development and limitations of using exosomes in cancer immunotherapy and our perspectives on how nanomaterials with potential immune regulatory effects could be introduced into exosome-based immunotherapy.